Perjanjian Pembiayaan Dengan Sistem Bagi Hasil Melalui Baitul Maal Wat Tamwil = FinancinAgreement By Profit Sharing System In Baitul Maal Wat Tamwil - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
Research about Financing Agreement by Profit Sharing System in Baitul Maal Wat Tamwil was a normative juridical research, that was a research that based on library research. The purposes of this research were: 1. to find out the way of making financing agreement by profit sharing in BMT. 2. to find out the performance of profit sharing system in financing agreement in BMT. 3. to find out the settlement if the debitor didn't perform his obligation. The conclusions of this research were: 1. financing agreement between BMT and debitor was made written that form and its contents had been fixed by BMT before. So, the financing agreement between BMT and debitor did not have to be done at BMT. The making of financing agreement between BMT and debitor can be done at debitor's place. 2. the financing that used syirkah agreement (profit sharing) were mudharabalz and musyarakah. To fix profit sharing for the financing by syirkah principle was by fix the portion of profit sharing in the beginning of the agreement. Usually there were two ways that were used as base in taking profit sharing, they were revenue or profit. 3. in case debitor didn't perform hiS obligation then BMT settled with silahturahmi. It was meant to keep the good relationship between BMT and debitor. BMT in handled debitor who didin' t perform his obligation never go to the court, because the settlement in court would need a long time and a big cost.